The 43rd Annual IEEE Symposium on Foundations of Computer Science, 2002. Proceedings.
DOI: 10.1109/sfcs.2002.1181944
|View full text |Cite
|
Sign up to set email alerts
|

An information statistics approach to data stream and communication complexity

Abstract: We present a new method for proving strong lower bounds in communication complexity. This method is based on the notion of the conditional information complexity of a function which is the minimum amount of information about the inputs that has to be revealed by a communication protocol for the function. While conditional information complexity is a lower bound on the communication complexity,we show that it also admits a direct sum theorem. Direct sum decomposition reduces our task to that of proving (conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
526
0

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(536 citation statements)
references
References 23 publications
10
526
0
Order By: Relevance
“…This shows that the Hss algorithm described in this section for estimating , is nearly space optimal for = 0 or 1 and ∈ [1,2]. The problem of obtaining lower bounds for estimating , for ∈ (0, 2) and ∈ (0, 2), (with the exception of the above cases) is open.…”
Section: Similarly Ifmentioning
confidence: 94%
See 2 more Smart Citations
“…This shows that the Hss algorithm described in this section for estimating , is nearly space optimal for = 0 or 1 and ∈ [1,2]. The problem of obtaining lower bounds for estimating , for ∈ (0, 2) and ∈ (0, 2), (with the exception of the above cases) is open.…”
Section: Similarly Ifmentioning
confidence: 94%
“…Thus, ∑ =1 0 , counts the number of distinct sources that send at least one message to . Define the hybrid moment 0,2 ( ) = ∑ =1 ( ∑ =1 0 , ) 2 . In an attack scenario, 0,2 ( ) becomes large compared to its average value.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is tight following successively improved lower bounds from [14], via e.g. [196] and [21], to finally [31].…”
Section: Moments Estimationmentioning
confidence: 96%
“…The reader familiar with the techniques of Bar-Yossef, Jayram, Kumar & Sivakumar [BYJKS04], should recall that in the first part of the method a direct-sum for informational complexity of disjointness is proved. In particular, it is shown that with respect to suitable collections of distributions η and ζ for DISJ n,2 and AND 2 respectively, the information cost of DISJ n,2 is at least n times the informational complexity of AND 2 : IC η,δ (DISJ n,2 ) ≥ n · IC ζ,δ (AND 2 ).…”
Section: Difficulties In Proving a Direct-sum Theoremmentioning
confidence: 99%